FEATURES OF CIVIL SOCIETY IN THE KYRGYZ REPUBLIC (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
The study of this topic is of very wide interest, both from the scientific intelligentsiaand from the political elite. Civil society is considered a measure of the level of development. Thisis especially true of the post-Soviet countries, which only appeared on the world map just overtwenty years ago. In the Soviet Union, the very concept of civil society was not used in relation toSoviet society.The newly independent states faced the need to develop their own conceptual foundationsfor building a civil society that adequately meets the needs of their development in the changedconditions. Taking into account the heterogeneity of the composition and the diversity of the political and socio-economic aspirations of the new states, the nature and dynamics of the processesof building civil society developed in them in different ways. In a number of other countries, theevents in the post-Soviet period were characterized by acute drama, up to the outbreaks of the socalled color revolutions, which radically changed the political structure of society and the guidelines of socio-economic development in them. As time has shown, civil society plays an importantrole in the development of the state.This article provides a scientific analysis of the role of theinstitute of civil society in the Kyrgyz Republic.
Keywords: civil society, sovereign state, USSR, social state, political system, state institutions, political power, consumer society, political organization, sovereignty.